The objective is quality : introduction to quality, performance and sustainability management systems - Jaccard, Michel (EPFL Press, 2013)
Quality is a form of management that is composed of the double approach of driving an organization towards excellence, while conforming to established standards and laws. The objective of quality confers advantages to companies: it makes them more resilient to change that can be unexpected or even chaotic; it makes them more competitive by identifying those steps in processes that do not offer added value. No longer the concern of a small community of experts, even scientists and engineers working in the private sector will find that they will have to con- front questions related to q.